Modeling OFF-state harmonics in MOS transistors used as RF switches. (November 2020) - Niemeier, Dennis; Feick, Henning; Bartels, Martin; Cattaneo, Andrea; Malkov, Nikita
Highlights: A calibrated TCAD harmonic balance simulation is used to locate nonlinear regions. New physics-based capacitance models for RF MOSFET in OFF-state are developed. The overlap capacitance nonlinearity is shown to dominate the OFF-state harmonics. The new overlap capacitance model is compared to established ones from BSIM and EKV. Abstract: In this paper we identify the dominant contribution to the OFF-state distortion of an MOS transistor coming from the overlap regions applying of device-level harmonic balance simulations in a calibrated TCAD setup. Both overlap ( C gs, C gd ) and direct capacitance ( C ds ) are described with novel physics-based models that are, in conjunction with an analytical Volterra series analysis, capable of describing the harmonics. This includes the dependency on process and device design parameters such as gate oxide thickness, DC gate bias and doping profile properties in the gate overlap region. The new model is compared to the overlap models of BSIM and EKV showing superior accuracy in modeling the harmonics qualitatively and quantitatively (within < 3  dBm for the second and < 5  dBm for the third harmonic, respectively).